A target-oriented DEA model for regional construction productive efficiency improvement in China. (January 2021) - Luo, Ming; Fan, Hongqin; Liu, Guiwen
Highlights: DEA and distance friction minimization are used to identify the causes of inefficiency and sources of growth in regional construction industry of China. Target-oriented approach is applied to set stagewise targets and plan for an incremental improvement of regional construction productive efficiency. Stepwise growth of construction productive efficiency is more practical due to the complex nature of construction industry. Recommendations are made for policy formulation and strategic planning in regional construction industry of China. Abstract: China's construction industry is a major contributor to economic growth during the past decade, but the industry has been mainly investment-driven without significant productivity improvement yet with high disparity across different regions. In the context of unbalanced regional development and resource allocation, stagnant performance of construction productivity is a common concern hindering the rapid and sustainable development of regional construction industry. The long-standing and escalating regional differences would not only undermine the overall performance of construction productivity, also lead to inefficient resource allocation and inappropriate target settings for future development. To address these issues, this study developed an overall efficiency measurement model for the construction industry, and then applied a Target-Oriented (TO) Data Envelopment Analysis (DEA) model to identify the optimal pathways for low efficiency provinces with the achievement of stage-wise targets in different regions of China. Comparison was made on construction productive efficiency, resource utilization, and recommendations were made for further improvement in three regions with different levels of economic development. The analytical and empirical results can provide insightful information for policy making and strategic planning with progressive efficiency improvement of regional construction industry of China.